Highly thermally conductive slurry composition and method thereof
Patent Information
- Application Number
- JP2024546060
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-01
- Filing Date
- 2023-01-25
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-01-25
Smart Images

Figure 2025505597000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims priority to co-pending U.S. Provisional Patent Application No. 63 / 305,639, filed February 1, 2022, which is incorporated herein by reference.
[0002] The field of the invention is compositions and methods for heat transfer in geothermal heat recovery, and in particular, compositions with high thermal conductivity that can be deployed / installed in very high temperature wells. [Background technology]
[0003] The background discussion contains information useful in understanding the present invention. No admission is made that any of the information provided herein is prior art or relevant to the presently claimed invention, or that any publication specifically or implicitly referenced is prior art.
[0004] All publications and patent applications herein are incorporated by reference to the same extent as if each individual publication or patent application was specifically and individually indicated to be incorporated by reference. If a definition or use of a term in an incorporated reference contradicts or is contrary to the definition of that term provided herein, the definition of that term provided herein shall apply and the definition of that term in the reference shall not apply.
[0005] Geothermal wells have been used to provide heating and cooling systems that transfer heat to and from the earth. In a typical vertical well closed loop system, two pipes joined with a U-shaped connector at the bottom, forming a continuous casing, are installed vertically in a well drilled into the earth (see U.S. Patent Application Publication No. 2012 / 0247766). This type of system is typically used for heating and cooling residential and commercial buildings. Here, a conventional grout mixture is clay-based and is pumped into the well to fill the annular space between the casing and the earth formation. As a result, the grout forms a seal to prevent contamination of the groundwater and to prevent contamination of the subsurface from above ground. The grout mixture may further include a thermally conductive material that aids in the heat transfer between the working fluid in the casing and the target location, and the working fluid may circulate in the well loop to transfer heat to and from a heat exchanger at the surface.
[0006] In most cases, conventional grout mixtures are hardenable in the presence of heat. However, while conventional geothermal wells are shallow below the surface and effective at providing heating or cooling to locations (e.g., heat exchangers) in close proximity to the wells through heat transfer, geothermal well systems for geothermal power generation require significant depths (e.g., at least 500 feet) underground and / or close proximity to known geothermal hot zones (e.g., crustal plate boundaries) to reach target locations suitable for obtaining the thermal energy required for power generation. Such target locations may exhibit extreme temperatures (e.g., 300° C.), which may lead to premature hardening of conventional grout mixtures and generally fail to provide sufficiently high thermal conductivity to make power generation ineffective or even feasible.
[0007] Furthermore, because the grout mixture must be cured after installation in a conventional geothermal well, the grout mixture typically contains a significant amount of curable material (e.g., cementitious material) for the curing of the grout mixture. Unfortunately, these curable materials do not exhibit high thermal conductivity, so even if the grout composition contains some thermally conductive material, a significant portion of the grout composition lacks thermal conductivity at best and acts as an insulator at worst. Thus, all or almost all grout compositions formed from conventional grout mixtures are unable to efficiently conduct the thermal energy required for power generation and also unable to maintain workability during construction at the extreme temperatures (e.g., 300° C.) near the target location for power generation (e.g., geothermal energy source).
[0008] Granular mixtures that do not include a hardenable material have been utilized in certain underground applications, such as plugging underground pipes (see, for example, U.S. Patent Nos. 6,715,543 and 7,258,174). Although these granular mixtures do not include a hardenable material, the granular mixtures lack high thermal conductivity and are generally not suitable for application at extreme temperatures (e.g., 300°C) near target locations (e.g., geothermal energy sources). On the other hand, certain grout mixtures are disclosed in U.S. Patent Application No. 2021 / 0071063 that are comprised of a hardenable component combined with a thermally conductive material having multiple particle sizes to form a hardened thermally conductive material with low water permeability. However, such mixtures are generally not suitable for heat harvesting, where the extracted heat is used to generate electricity, since the thermal conductivity is still relatively low.
[0009] US Patent Application 2011 / 0232858 teaches a system and method for extracting heat for power generation from high temperature (e.g., 500°C) earth formations, in which one or more boreholes contain a thermally conductive compressed filler that conducts heat to a piping system at a target location, where the compressed filler is graphite formulated as a powder or rod. To reduce the occurrence of voids that can act as thermal insulators, the '858 application relies on high pressure molding. Thus, while multiple and / or extensive carbon-filled conduits can be formed in the formation, the heat transfer to the working fluid in a tube-in-tube system is typically limited to the end portions of the system (because the compression pressure would otherwise crush the tube-in-tube system), thereby significantly reducing the overall heat extraction. The use of multiple converging graphite-filled channels in a tube-in-tube system can increase heat extraction, but such an increase increases the complexity and cost of operations.
[0010] Thus, although a variety of compositions for geothermal heat transfer compositions are known in the art, all or nearly all of them suffer from several drawbacks. Thus, there remains a need for highly thermally conductive compositions and methods for transferring heat therefrom. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] US Patent Application No. 2012 / 0247766 [Patent Document 2] U.S. Patent No. 6,715,543 [Patent Document 3] U.S. Patent No. 7,258,174 [Patent Document 4] U.S. Patent Application No. 2021 / 0071063 [Patent Document 5] US Patent Application No. 2011 / 0232858 Summary of the Invention [Problem to be solved by the invention]
[0012] The subject matter of the present invention is directed to various high thermal conductivity slurry compositions and methods of producing pumpable slurries forming such high thermal conductivity compositions. Advantageously, the high thermal conductivity compositions are typically formed from non-cementitious slurry mixtures, and they can be utilized in encasement applications in heat wells, particularly closed loop geothermal system wells for geothermal power generation. The envisaged high thermal conductivity compositions facilitate installation, advantageously improve the heat transfer per unit length of the well from the target location, and maintain structural integrity even after seismic events. This improved heat transfer allows for greater capture of thermal energy into the working fluid, increasing the revenue of the power generating well.
[0013] In one aspect of the present subject matter, the inventors contemplate a highly thermally conductive slurry composition comprising a slurry mixture. The slurry composition comprises a highly thermally conductive material in the form of a plurality of particles having a broad particle size distribution that allows for tight settling / compaction at the target location, thereby thermally coupling with the formation through the casing and optional dispersant. In various embodiments, the slurry mixture has a deposition rate of the plurality of particles that allows it to be pumped to the target location upon addition of water without substantial settling of the particles prior to reaching the target location.
[0014] It is contemplated that the high thermal conductivity material is in the form of a plurality of particles having a broad particle size distribution spanning at least 2 log units or at least 3 log units. In various embodiments, the broad particle size distribution is 0.1 μm to 5.0 mm. In further embodiments, it is contemplated that the high thermal conductivity material may be present in an amount effective to cause the slurry composition to have a thermal conductivity of at least 3 W / m°K, at least 3 W / m°K, or at least 10 W / m°K upon compression or settling of the slurry mixture at the target location. Among other options, suitable high thermal conductivity materials include graphite powder, flake graphite, pyrolytic graphite, desulfurized petroleum coke, graphene, fly ash, copper powder, aluminum nitride, and / or silicon carbide. Most typically, the high thermal conductivity material is present in the slurry mixture in an amount of at least 10% by weight, or at least 30% by weight, by volume. In certain embodiments, the slurry mixture may also include at least one functional agent, contemplated functional agents include plasticizers, surfactants, organic polymers, silica fillers, NaCl or KCl or other inorganic salts, and clays.
[0015] Referring to the pumpable slurry, the pumpable slurry preferably comprises a high thermal conductivity slurry composition miscible with water. The pumpable slurry can typically have a density of 10-30 pounds per gallon and / or a water content of 1-20 gallons per 100 pounds of high thermal conductivity material. As will be readily understood, the pumpable slurry can be produced by combining the high thermal conductivity slurry composition with a large amount of water and mixing the water with the high thermal conductivity slurry composition, thereby forming a pumpable slurry. In various embodiments, the amount of water is sufficient to produce a slurry density of 10-30 pounds per gallon. It is further envisioned that the pumpable slurry can be fed to a pump that pumps the pumpable slurry to the wellbore. Most typically, the pumpable slurry is pumped to the wellbore at a rate that allows for at least partial compaction or settling of the slurry mixture at the target location.
[0016] Referring to the installation of the high thermal conductivity composition, the method of installation typically includes pumping a pumpable slurry to a target location having a target temperature of at least 300° C. The pumpable slurry is preferably delivered into an annular space between a wellbore and a casing located within the wellbore, thereby displacing fluid within the annular space. In some embodiments, the target location may be at least 3,000 feet below ground and / or may extend substantially vertically.
[0017] Contemplated methods further include removing the displaced fluid through a return space located within the casing. The return space located within the casing may be enclosed within a secondary conduit located within the casing, and a second annular space may be formed between the casing and the secondary conduit. Thus, the step of removing the displaced fluid through the return space may use a second fluid moving from the second annular space to the return space.
[0018] Contemplated methods may further include allowing the pumpable slurry to settle or compress within at least a portion of the annular space, thereby forming a highly thermally conductive composition within the wellbore. It is contemplated that the highly thermally conductive composition exchanges heat with at least a portion of the casing and at least a portion of the formation surrounding the wellbore. To this end, the pumpable slurry is pumped to a predetermined location and, after pumping, is allowed to undergo at least partial compression of the slurry (by passive settling or active compression) at the target location.
[0019] In certain embodiments, it is envisioned that the formation includes a plurality of fractures at least partially filled with a high thermal conductivity material, and the high thermal conductivity material in the fractures exchanges heat with the compressed high thermal conductivity composition in the wellbore. Among other options, suitable high thermal conductivity materials in the fractures include graphite powder, flake graphite, pyrolytic graphite, desulfurized petroleum coke, graphene, fly ash, copper powder, aluminum nitride, and silicon carbide.
[0020] Various objects, features, aspects and advantages of the present subject matter will become more apparent from the following detailed description of preferred embodiments, taken in conjunction with the accompanying drawing figures in which like numerals represent like elements. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a schematic diagram illustrating an embodiment of a geothermal well including a wellbore during installation of a pumpable slurry. [Diagram 2] FIG. 2 is a schematic diagram illustrating the geothermal well embodiment of FIG. 1 after compression or settling of at least a portion of the pumpable slurry. [Diagram 3] FIG. 3 is a schematic diagram illustrating the well and casing embodiment of FIG. 1 deployed in a geothermal well. [Figure 4] FIG. 4 is a schematic diagram illustrating another embodiment of the well and casing of FIG. 1 deployed in a geothermal well. [Diagram 5] FIG. 5 is a schematic diagram illustrating yet another embodiment of the well and casing of FIG. 1 deployed in a geothermal well. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The inventors have discovered various compositions for high thermal conductivity slurries and methods of making pumpable slurries including the same, as well as methods of installing high thermal conductivity compositions including the same. Advantageously, the high thermal conductivity slurry compositions are pumpable and formed from a slurry mixture that can be utilized in encasement applications in heat wells, such as closed loop geothermal system wells, and have suitable thermal conductivity for power generation. Additionally, the contemplated compositions do not require hardenable materials (e.g., cementitious materials), resulting in improved workability of the pumpable slurries, improved thermal efficiency of the high thermal conductivity compositions, and increased power generation in power generating wells. Thus, it should be appreciated that in at least some embodiments, the contemplated compositions do not exhibit hardening or curing due to hydration of cementitious materials. As a result, the contemplated compositions remain deformable or movable without the formation of fractures and / or loss of contact with the wellbore or casing.
[0023] In the most typical embodiment of the subject matter of the present invention, the slurry mixture of the high thermal conductivity slurry composition comprises a high thermal conductivity material and an optional dispersant, and the high thermal conductivity material is in the form of a plurality of particles having a broad particle size distribution spanning at least 2 log units, at least 2.5 log units, or at least 3 log units. In this context, it should be understood that the broad particle size distribution of the high thermal conductivity material stabilizes the form or configuration of the high thermal conductivity composition upon compaction or settling of the slurry mixture without the use of a hardening material (e.g., a cement-based material), thereby reducing the permeability of liquids through the high thermal conductivity composition compared to a composition comprising particles with a narrow particle size distribution. As used herein, the terms "compacted" and / or "settled" mean that the compacted or settled slurry mixture is mobile in the presence of substantial forces (e.g., earthquakes) while (a) having a reduction in moisture content of at least 1%, 2%, 3%, 4%, 5%, 10%, 20%, 30%, 40%, 60%, 70%, 80%, 90% by weight compared to the slurry mixture prior to compaction or settlement, (b) having an increase in density of at least 1%, 2%, 3%, 4%, 5%, 10%, 15%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100% or more by weight compared to the slurry mixture prior to compaction or settlement, or (c) having both (a) a reduction in moisture content and (b) an increase in density. Additionally, it should be noted that in some embodiments, contemplated slurry compositions may settle over time without the need for an active compaction step, while in other embodiments, the slurry compositions may be actively compacted (e.g., via a pressure increase at the target location).
[0024] The particle size distribution in the slurry mixture of the highly thermally conductive material can be represented by the concept of sorting. The concept of sorting may be a qualitative measure of the degree of variation, or the range of variation, of different particle sizes in a mixture of unconsolidated materials (e.g., the highly thermally conductive material of the slurry mixture). A poorly sorted mixture of unconsolidated materials may contain a large spectrum of particle sizes, such as particles in the particle size range of gravel, sand, silt, and clay. In comparison, a moderately sorted mixture of unconsolidated materials may contain a small spectrum of particle sizes, such as medium and fine sand, while a very well sorted mass may contain only one relatively homogeneous particle size, such as coarse silt. In view of the foregoing, the slurry mixture may contain a poorly sorted mixture of highly thermally conductive materials that, upon compaction or settling of the slurry mixture, exhibits a reduced permeability of liquids through the highly thermally conductive composition, as compared to a composition containing particles having at least a moderately sorted mixture of unconsolidated materials. In various embodiments, the high thermal conductivity material can have an average particle size of 0.1 μm to 5.0 mm.
[0025] After compaction or settling of the slurry mixture, it is envisioned that the high thermal conductivity materials of the high thermal conductivity composition will settle or pack together in such a manner that the broad particle size distribution of the high thermal conductivity materials minimizes fluid migration through the high thermal conductivity composition. In various embodiments, the high thermal conductivity composition has a permeability of 1 darcy or less, 0.1 darcy or less, 0.01 darcy or less, 0.001 darcy or less, or 0.0001 darcy or less, according to ASTM D4630-19. According to ASTM D4630-19, 1 darcy is defined as the permeability of a material at a pressure differential of 1 atm per cm length (1 atm / 1 cm) through a cross-sectional area of 1 cm. 2 Flow rate per 1cm 3 / s (1cm 3 / s / 1cm 2 ), which corresponds to a fluid with a viscosity of 1 cp flowing through a porous medium. In this sense, it should be understood that this index is considered a proxy for interparticle contact (a lower Darcy number indicates greater interparticle contact) and thus represents the thermal conductivity between particles.
[0026] It is generally assumed that the particle size distribution of the high thermal conductivity material particles is effective for forming a fluid seal in the annular space between the well and the casing of the heat harvester in the well. Typical particle size distributions are described in U.S. Patent Nos. 6,715,543 and 7,528,174, which are incorporated herein by reference. Thus, it is generally preferred that the particles have an average particle size of 0.1 μm to 5 mm, with at least 90% of all particles having an average particle size that falls within a particle size range that spans at least two orders of magnitude, or at least three orders of magnitude, or at least four orders of magnitude. For example, suitable average particle size ranges are 0.1 mm to 10 mm, or 50 μm to 5 mm, or 5 μm to 5 mm, or 1 μm to 1 mm, or 10 μm to 5 mm. Further, the particle size distribution is such that at least 20%, or at least 25%, or at least 30%, or at least 35%, or at least 40%, by weight, of all particles are within the lower 20%, or lower 25%, or lower 35% of the particle size range, while at least 10%, or at least 15%, or at least 20%, or at least 25%, or at least 30%, by weight, of all particles are within the upper 15%, or upper 20%, or upper 25% of the particle size range of all particles.
[0027] Thus, the majority of the particles by weight (at least 51%, or at least 60%, or at least 70%, or at least 75%) are in the millimeter to sub-millimeter (but not less than 50 μm) particle size range, while the remainder of the particles are in the particle size range below 50 μm. For example, about 80 mass percent of the total particles have average particle sizes of 0.5-1 mm, and 0.25-0.5 mm, 0.125-0.25 mm, and 0.0625-0.125 mm, about 20 mass percent of the total particles have an average particle size in the range of 5-65 μm, and about 50% of them are in the particle size range of about 5 μm. Viewed another way, the particle size distribution is such that at least 45%, or at least 50%, or at least 55%, or at least 60%, or at least 65%, by weight of all particles have a 20 / 40 mesh size, at least 10%, or at least 15%, or at least 20%, or at least 25%, or at least 30%, by weight of all particles have a 100 mesh size, at least 7%, or at least 10%, or at least 12%, or at least 15%, or at least 20%, by weight of all particles have a 200 mesh size, and at least 2%, or at least 3%, or at least 4%, or at least 5%, or at least 7%, by weight of all particles have an average particle size less than 25 μm.
[0028] Furthermore, since the highly thermally conductive composition is, in most embodiments, substantially free of hardenable materials (e.g., cementitious materials), it should be appreciated that the highly thermally conductive composition remains mobile and / or deformable in the presence of substantial forces (e.g., earthquakes, thermal expansion and / or contraction of the casing of the heat harvesting device embedded in the highly thermally conductive material) to minimize damage to the geothermal well containing the highly thermally conductive composition. Such deformability is particularly beneficial in cases where geological stresses or temperature fluctuations in the heat harvesting structure would otherwise cause cracks in the cured or hardened material. In fact, the mobility and / or deformability of the highly thermally conductive composition ensures continuous contact between the highly thermally conductive composition and the heat harvesting structure encased in the highly thermally conductive composition. Furthermore, the workability of the slurry mixture of the highly thermally conductive slurry composition is improved, allowing the slurry composition to be placed in the well even under extreme temperature conditions (e.g., at least 300° C.) resulting from the slurry mixture being substantially free of certain hardenable materials (e.g., cementitious materials). Furthermore, it should be appreciated that due to the relatively broad particle size distribution, voids created by larger particles are easily filled by smaller particles, resulting in significantly improved thermal conductivity.
[0029] The inventors further contemplate that the high thermal conductivity material is present in an amount effective to cause the slurry composition to have a thermal conductivity of at least 1 W / m°K, at least 4 W / m°K, at least 10 W / m°K, at least 15 W / m°K, at least 20 W / m°K, at least 25 W / m°K, at least 35 W / m°K, and at least 40 W / m°K upon compression or settling of the slurry mixture at the target location. Without being bound by theory, it is contemplated that the compression or settling of the slurry mixture due to the broad particle size distribution of the high thermal conductivity material provides the high thermal conductivity composition with improved thermal conductivity compared to a composition including particles with a narrow particle size distribution. Thus, viewed alternatively, any given volume of the settling or compressed high thermal conductivity material has no more than 15%, no more than 10%, no more than 8%, no more than 6%, no more than 5%, no more than 4%, no more than 3%, no more than 2% of the given volume as voids.
[0030] As will be appreciated, the high thermal conductivity material used provides an increased thermal conductivity of the high thermal conductivity composition formed from the slurry mixture, and therefore provides the geothermal well loop with the ability to extract heat more efficiently during operation, as compared to all, or nearly all, known grout compositions. Suitable high thermal conductivity materials include, but are not limited to, graphite, sand, quartz silica, carbon nanotubes, graphene, boron nitride, brass, brass alloys, chrome nickel steel, carbon steel, stainless steel, transition metals (e.g., copper, cadmium, cobalt, gold, silver, iridium, iron, molybdenum, nickel, platinum, zinc, etc.), transition metal alloys (e.g., copper alloys, cadmium alloys, zinc alloys, etc.), copper alloys, cadmium alloys, cobalt alloys, gold alloys, silver alloys, iridium alloys, iron alloys, molybdenum alloys, nickel alloys, platinum alloys, zinc alloys, etc.), post-transition metals (e.g., lead, tin, etc.), post-transition metal alloys (e.g., lead alloys, tin alloys, etc.), alkaline earth metal alloys (e.g., beryllium alloys, magnesium alloys, etc.), or combinations thereof. In certain embodiments, the high thermal conductivity material is a carbon allotrope, with specifically contemplated allotropes including graphite powder, exfoliated graphite, flaked graphite, pyrolytic graphite, desulfurized petroleum coke, graphene, fly ash, copper powder, aluminum nitride, silicon carbide, and combinations thereof.
[0031] In some embodiments, the high thermal conductivity material can be present in the slurry mixture of the high thermal conductivity slurry composition in an amount sufficient to provide the desired thermal conductivity to the high thermal conductivity slurry of the geothermal well. The high thermal conductivity material can be present in the slurry mixture in an amount of at least 5%, or 10%, or 20%, or 25%, or 30%, or 35%, or 40%, or 45%, or 50%, or 55%, or 60%, or 65%, or 70%, or 75%, or 75%, or 80%, or 85%, or even more by weight based on the total weight of the slurry mixture. Alternatively, the high thermal conductivity material may be present in the slurry mixture in an amount of up to 80%, 70%, 60%, 50%, 45%, 40%, 35%, 20%, 15%, or 10% by weight based on the total weight of the slurry mixture, or from about 50 to about 80%, from about 55% to about 85%, or from about 60% to about 90% by weight based on the total weight of the slurry mixture.
[0032] Thus, in some embodiments, the high thermal conductivity composition formed from a slurry mixture of the high thermal conductivity slurry composition comprising the high thermal conductivity material has a thermal conductivity of at least 0.5 British Thermal Units per Foot per Hour per Degree Fahrenheit (BTU / hr·ft·°F), at least 0.57 BTU / hr·ft·°F (1 W / m°K), at least 1.73 BTU / hr·ft·°F (3 W / m°K), at least 2.0 BTU / hr·ft·°F, at least 2.31 BTU / hr·ft·°F (4 W / m°K), at least 4.0 BTU / hr·ft·°F, at least 5.78 BTU / hr·ft·°F, at least 6.5 BTU / hr·ft·°F, at least 7.5 BTU / hr·ft·°F, at least 8.5 BTU / hr·ft·°F, at least 9.5 BTU / hr·ft·°F, at least 10 ... U / hr·ft·°F (10 W / m°K), at least 6.0 BTU / hr·ft·°F, at least 8.0 BTU / hr·ft·°F, at least 10 BTU / hr·ft·°F, at least 12 BTU / hr·ft·°F, at least 14 BTU / hr·ft·°F, at least 16 BTU / hr·ft·°F, at least 20 BTU / hr·ft·°F, at least 20 BTU / hr·ft·°F, at least 25 BTU / hr·ft·°F, at least 30 BTU / hr·ft·°F, or at least 40 BTU / hr·ft·°F or even higher. Alternatively, the high thermal conductivity composition formed from the slurry mixture including the high thermal conductivity material has a thermal conductivity of 30 BTU / hr·ft·°F or less, 25 BTU / hr·ft·°F or less, 20 BTU / hr·ft·°F or less, 18 BTU / hr·ft·°F or less, 16 BTU / hr·ft·°F or less, 14 BTU / hr·ft·°F or less, 12 BTU / hr·ft·°F or less, or 10 BTU / hr·ft·°F or less.
[0033] It is contemplated that, if the contemplated composition includes a dispersant, the dispersant may be present in the slurry mixture of the high thermal conductivity slurry composition and may act as a thinner or deflocculating agent to improve the workability of the high thermal conductivity slurry composition. In some embodiments, the dispersant may include, but is not limited to, acid derivatives, salts of acid derivatives, phosphates, sodium carbonate, polymeric or monomeric sodium silicate complexes (e.g., sodium metasilicate, water glass, etc.), lignite compounds, and low molecular weight polymers, soaps, surfactants, sulfonates, or combinations thereof.
[0034] Acid derivatives that may be used as dispersants in the slurry mixture include, but are not limited to, derivatives of tannic acid, derivatives of citric acid (e.g., citrate), derivatives of humic acid, derivatives of phosphoric acid, disodium hydrogen phosphate, trisodium phosphate, dihydrogen phosphate, quebracho, derivatives of quebracho, sulfomethylated quebracho, derivatives of sulfomethylated quebracho, alkylated quebracho, derivatives of alkylated quebracho, naphthalenesulfonic acid condensed with formaldehyde, and any combination thereof. Salts of these acid derivatives may also be suitable as dispersants (e.g., sodium salts of acid derivatives), including, but not limited to, sodium humate, sodium phosphate, sodium citrate, sodium tannate, and the like, and any combination thereof. Phosphates suitable for use as dispersants include, but are not limited to, sodium polyphosphate, tetrasodium polyphosphate, sodium tripolyphosphate, sodium hexametaphosphate, sodium acid pyrophosphate, sodium metaphosphate, sodium hexametaphosphate, and any combination thereof. Suitable lignite compounds include, but are not limited to, lignosulfonates, alkali lignosulfonates (e.g., alkaline earth metals such as sodium, potassium, or calcium), acrylic lignosulfonates, causticized lignite, causticized leonardite, iron lignosulfonate, chromium lignosulfonate, iron-chromium lignosulfonate, transition metal lignosulfonates (e.g., zirconium lignosulfonate, titanium lignosulfonate, etc.), sulfoalkylated lignite, or combinations thereof.
[0035] Examples of suitable low molecular weight polymers include polyacrylates, alkali salts of polyacrylic acid, poly(sulfonated styrene-co-maleic anhydride), poly(acrylic acid-co-vinyl sulfonic acid), alkali salts of polymethacrylates, polyacrylamido-2-acrylamido-2-methylpropanesulfonic acid, the sodium salt of polyacrylamido-2-acrylamido-2-methylpropanesulfonic acid, polymers made from sulfonated condensed naphthalenesulfonic acid polymers, polymers of unsaturated dicarboxylic acids, polymers of monoethylenically unsaturated monocarboxylic acids, and polymers of ethylenically unsaturated monomers and polyalcohols. Examples of such polymers include, but are not limited to, graft polymers of xylene glycol, allyloxybenzenesulfonate polymers, alkylated polymeric salts of allyloxybenzenesulfonic acid, terpolymers of tetrahydrophthalic acid, acrylic acid, 2-acrylamido-2-methylpropanesulfonic acid and lignosulfonates, graft copolymers of tetrahydrophthalic acid, acrylic acid, 2-acrylamido-2-methylpropanesulfonic acid and lignosulfonates, organosilicon polymers, and the term "low molecular weight polymer" as used herein means a polymer having a molecular weight of less than 1,000,000.
[0036] Suitable soaps which may be used as dispersants include sodium stearate, potassium stearate, ammonium stearate, sodium aurate, potassium aurate, sodium myristate, potassium myristate, sodium ricinoleate, potassium ricinoleate, sodium palmitate, potassium palmitate, calcium caprylate, sodium caprylate, potassium caprylate, 4,7,10,13,16,19-docosahexaenoic acid, 4,7,10,13,16-docosapentaenoic acid, 5,8,11,14,17-eicosanoic acid, 5,8,11,14,17-tetrahydrofuran ... Sapentaenoic acid, 5,8,11,14-eicosatetraenoic acid, 5,8,11-eicosatrienoic acid, 6,9,12,15-octadecatetraenoic acid, 7,10,13,16,19-docosapentaenoic acid, 7,10,13,16-docosatetraenoic acid, 8,11,14,17-eicosatetraenoic acid, 8,11,14-eicosatrienoic acid, behenic acid, capric acid, caprylic acid, cis-11-docosenoic acid, cis-11-eicosenoic acid, cis-11-octadecenoic acid, cis-15-tetracosenoic acid, cis-4-decenoic acid, cis-4-dodecenoic acid, cis -4-Tetradecenoic acid, cis-5-lauroyl acid, cis-5-tetradecenoic acid, cis-6-octadecenoic acid, cis-9-decenoic acid, cis-9-dodecenoic acid, cis-9-eicosenoic acid, cis-9-hexadecenoic acid, cis-9-tetradecenoic acid, cis-tetracosenoic acid, caprylic acid, decenoic acid, dihydroxystearic acid, docosadienoic acid, docosahexaenoic acid, docosapentaenoic acid, dotriacontanoic acid, eicosadienoic acid, eicosanoic acid, eicosapentaenoic acid, eicosatetraenoic acid, eicosatrienoic acid, eicosenoic acid, erucic acid, heptadeca and combinations thereof.
[0037] Sulfonates suitable for use as dispersants include, but are not limited to, melamine sulfonate condensed with formaldehyde, sulfonated styrene maleic anhydride copolymer, sulfonated vinyl toluene maleic anhydride copolymer, sodium naphthalene sulfonate condensed with formaldehyde, sulfonated acetone condensed with formaldehyde, interpolymers of acrylic acid, allyloxybenzene sulfonate, allyl sulfonate, or combinations thereof.
[0038] In some embodiments, the dispersant may be present in the slurry mixture of the high thermal conductivity slurry composition in an amount sufficient to impart a desired viscosity to the slurry mixture. The dispersant may be present in the slurry mixture in an amount of at least 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight based on the total weight of the slurry mixture. Alternatively, the dispersant may be present in the slurry mixture in an amount of 20% or less, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, or 10% by weight based on the total weight of the slurry mixture. Alternatively, the dispersant may be present in the slurry mixture in an amount of about 1 to about 20%, about 5% to about 15%, or about 7% to about 13% by weight based on the total weight of the slurry mixture.
[0039] The slurry mixture of the high thermal conductivity slurry composition may further include at least one functional agent. The functional agent can be used to modify the rheological properties of the slurry mixture or to improve the mixability of the slurry mixture in response to various stimuli, such as temperature, pressure, contact with another material, or a combination thereof. The functional agent may be selected from the group consisting of plasticizers, surfactants, organic polymers, silica fillers, NaCl, KCl or other inorganic salts, clays, and combinations thereof.
[0040] A plasticizer may be present in the slurry mixture of the high thermal conductivity slurry composition to improve workability for ease of installation. In various embodiments, the term "plasticizer" refers to a substance that improves the flowability of the slurry mixture, thereby improving the workability of the slurry mixture, or allows the slurry mixture to be produced with less water while maintaining comparable workability. Suitable plasticizers include, but are not limited to, polycarboxylic ether plasticizers, phthalate plasticizers, terephthalate plasticizers, sulfonamide plasticizers, benzoate plasticizers, phosphate plasticizers, or combinations thereof.
[0041] In some embodiments, the plasticizer may be present in the slurry mixture of the high thermal conductivity slurry composition in an amount sufficient to provide the slurry mixture with desired workability. The plasticizer may be present in the slurry mixture in an amount of at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight based on the total weight of the slurry mixture. Alternatively, the plasticizer may be present in the slurry mixture in an amount of 20% or less, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, or 10% by weight based on the total weight of the slurry mixture. Alternatively, the plasticizer may be present in the slurry mixture in an amount of about 1 to about 20%, about 5% to about 15%, or about 7% to 13% by weight based on the total weight of the slurry mixture.
[0042] A surfactant may be present in the slurry mixture of the high thermal conductivity slurry composition to improve the surface properties of the slurry mixture. Suitable surfactants include, but are not limited to, nonionic surfactants, anionic surfactants, cationic surfactants, zwitterionic surfactants, or combinations thereof.
[0043] Suitable nonionic surfactants include alkoxylates (e.g., alkoxylated nonylphenol condensates such as poly(oxy-1,2-ethanediyl), alpha-(4-nonylphenyl)-omega-hydroxy-branched), alkylphenols, ethoxylated alkylamines, ethoxylated oleates, tall oil, ethoxylated fatty acids, alkyl polyglycosides, These include, but are not limited to, sorbitan esters, methyl glucoside esters, amine ethoxylates, diamine ethoxylates, polyglycerol esters, alkyl ethoxylates, polypropoxylated and / or polyethoxylated alcohols, linear alcohol alkoxylates, dodecylbenzene sulfonate derivatives, linear nonyl-phenols, dioxane, ethylene oxide, polyethylene glycols, ethoxylated castor oil, polyoxyethylene nonylphenol ethers, tetraethylene glycol dodecyl ether, ethylene oxide, decylamine oxide, dodecylamine oxide, alkylamine oxides, ethoxylated amides, alkoxylated fatty acids, alkoxylated alcohols (e.g., lauryl alcohol ethoxylate, ethoxylated nonylphenol), ethoxylated fatty amines, ethoxylated alkylamines (e.g., coco alkylamine ethoxylate), any derivatives thereof, and any combinations thereof. As used herein, the term "derivative" refers to any compound prepared from one of the compounds, for example, by replacing one atom in the named compound with another atom or group of atoms, or by rearranging two or more atoms in the compound.
[0044] Suitable anionic surfactants include alpha sulfo fatty acid methyl ester salts. sulfonate), hydrolyzed keratin, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, alkyl ether sulfate, sodium 4-(1'heptylnonyl)benzenesulfonate, sodium dioctyl sulfosuccinate, sodium octylbenzenesulfonate, sodium hexadecyl sulfate, sodium laureth sulfate, quaternary ammonium compounds (e.g., trimethylcocoammonium chloride, trimethyltallowammonium chloride, dimethyldicocoammonium chloride, etc.), cetylpyridinium chloride, alkyl ester sulfonates, alkyl ether sulfonates, alkyl ether sulfates, alkali metal alkyl sulfates, alkyl sulfonates, alkylaryl sulfonates, sulfosuccinates, alkyl disulfonates, alkylaryl disulfonates, alkyl disulfates, alcohol polypropoxylated sulfates, alcohol polyethoxylated sulfates, any derivatives thereof, and any combinations thereof.
[0045] Suitable zwitterionic surfactants include, but are not limited to, alkylamine oxides, alkylbetaines, alkylamidopropylbetaines, alkylsulfobetaines, alkylsultaines, dihydroxyalkylglycinates, alkylamphoacetates, phospholipids, alkylaminopropionic acids, alkyliminomonopropionic acids, alkyliminodipropionic acids, dipalmitoyl-phosphatidylcholine, amine oxides, betaines, modified betaines, alkylamidobetaines (e.g., cocoamidopropyl betaine), and any combination thereof.
[0046] By way of example, surfactants that may exhibit viscoelastic properties include, but are not limited to, sulfosuccinates, taurates, amine oxides (e.g., amidoamine oxides), ethoxylated amides, alkoxylated fatty acids, alkoxylated alcohols, ethoxylated fatty amines, ethoxylated alkylamines, betaines, modified betaines, alkylamido betaines, quaternary ammonium compounds, alkyl sulfates, alkyl ether sulfates, alkyl sulfonates, ethoxylated esters, ethoxylated glycoside esters, alcohol ethers, any derivatives thereof, and any combinations thereof.
[0047] In some embodiments, the surfactant may be present in the slurry mixture of the high thermal conductivity slurry composition in an amount sufficient to impart the desired surface properties to the slurry mixture. The surfactant may be present in the slurry mixture in an amount of at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight based on the total weight of the slurry mixture. Alternatively, the surfactant may be present in the slurry mixture in an amount of 20% or less, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, or 10% by weight based on the total weight of the slurry mixture. Alternatively, the surfactant may be present in the slurry mixture in an amount of about 1 to about 20% by weight, about 5% to about 15% by weight, or about 7% to about 13% by weight based on the total weight of the slurry mixture.
[0048] Organic polymers may be present in the slurry mixture of the high thermal conductivity slurry composition to improve the properties of the slurry mixture. Suitable organic polymers include, but are not limited to, natural compounds, synthetic compounds, or combinations thereof. Non-limiting examples of suitable natural compounds include polysaccharides, such as cold water soluble polysaccharides and polysaccharide ethers, such as cellulose ethers, starch ethers (amylose and / or amylopectin and / or their derivatives), guar ethers, dextrins, or combinations thereof. Non-limiting examples of suitable synthetic compounds include protective colloids, such as one or more of polyvinylpyrrolidone and / or polyvinyl acetate, polyvinyl alcohol, melamine formaldehyde sulfonate, naphthalene formaldehyde sulfonate, block copolymers of propylene oxide and ethylene oxide, styrene-maleic acid and / or vinyl ether-maleic acid copolymers.
[0049] In some embodiments, the organic polymer may be present in the slurry mixture of the high thermal conductivity slurry composition in an amount sufficient to impart a desired amount of properties to the slurry mixture. The organic polymer may be present in the slurry mixture in an amount of at least 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, or 10 wt%, based on the total weight of the slurry mixture. Alternatively, the organic polymer may be present in the slurry mixture in an amount of 20 wt%, 19 wt%, 18 wt%, 17 wt%, 16 wt%, 15 wt%, 14 wt%, 13 wt%, 12 wt%, 11 wt%, or 10 wt%, based on the total weight of the slurry mixture. Alternatively, the organic polymer may be present in the slurry mixture in an amount of about 1 to about 20 wt%, about 5 wt% to about 15 wt%, or about 7 wt% to 13 wt%, based on the total weight of the slurry mixture.
[0050] Optionally, a silica filler may be present in the slurry mixture of the high thermal conductivity slurry composition to improve the properties of the slurry mixture. Suitable silica fillers may be pyrogenic silica or precipitated finely-divided silica. The silica filler may have a particle size of about 50 to about 10,000 angstroms, about 50 to about 400 angstroms, or about 100 to about 300 angstroms. The silica filler may be present in the slurry mixture in an amount of at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight based on the total weight of the slurry mixture. Alternatively, the silica filler may be present in the slurry mixture in an amount of up to 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, or 10% by weight based on the total weight of the slurry mixture. Alternatively, the silica filler may be present in the slurry mixture in an amount of from about 1 to about 20%, from about 5% to about 15%, or from about 7% to about 13% by weight based on the total weight of the slurry mixture.
[0051] Inorganic salts may be present in the slurry mixture of the high thermal conductivity slurry composition to improve the mixability of the slurry mixture. Suitable inorganic salts include, but are not limited to, NaCl, KCl, and the like. The inorganic salt may be present in the slurry mixture in an amount of at least 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, or 10 wt%, based on the total weight of the slurry mixture. Alternatively, the inorganic salt may be present in the slurry mixture in an amount of 20 wt% or less, 19 wt%, 18 wt%, 17 wt%, 16 wt%, 15 wt%, 14 wt%, 13 wt%, 12 wt%, 11 wt%, or 10 wt%, based on the total weight of the slurry mixture. Alternatively, the inorganic salt may be present in the slurry mixture in an amount of about 1 to about 20 wt%, about 5 wt% to about 15 wt%, or about 7 wt% to about 13 wt%, based on the total weight of the slurry mixture.
[0052] Clays may be present in the slurry mixture of the high thermal conductivity slurry composition to modify the fluidity of the slurry mixture. Suitable clays include smectite family clays, palygorskite-sepiolite phyllosilicate family clays, kaolinite-serpentine family clays, nontronite, bentonite, hectorite, attapulgite, fluormica, montmorillonite, beidellite, saponite, sepiolite, kaolinite, illite, cation exchanged versions thereof, or combinations thereof.
[0053] Of the suitable smectite group clays, including nontronite, montmorillonite, saponite, hectorite, and beederite, other smectite group clays suitable for use as aqueous swelling clays in the present disclosure include, but are not limited to, ariettite, ferrosaponite, sauconite, stevensite, swinefodite, volkonskoite, yahontovite, and any combination thereof. Suitable clays of the palygorskite-sepiolite phyllosilicic acid family include, but are not limited to, attapulgite, tupahsauchiite, windhaukite, yawfortierite, falconite, ferrisepiolite, raufrinite, and any combination thereof. Suitable clays from the kaolinite-serpentine family of aqueous swelling clays include, but are not limited to, kaolinite, greenalite, flypontite, halloysite, dickite, lizardite, manandonite, nacrite, cronstedtite, clinochrysotile, chrysotile, nepite, odinite, webskiite, pecoraite, orthochrysotile, parachrysotile, caryopilite, brindleyite, berthierine, amesite, antigorite, boehmite, and any combination thereof.
[0054] In some embodiments, the clay can be present in the slurry mixture of the high thermal conductivity slurry composition in an amount sufficient to impart a desired amount of properties to the slurry mixture. The clay may be present in the slurry mixture in an amount of at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight based on the total weight of the slurry mixture. Alternatively, the clay may be present in the slurry mixture in an amount of 20% or less, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, or 10% by weight based on the total weight of the slurry mixture. Alternatively, the clay may be present in the slurry mixture in an amount of about 1 to about 20%, about 5% to about 15%, or about 7% to about 13% by weight based on the total weight of the slurry mixture.
[0055] The slurry mixture of the high thermal conductivity slurry composition may include various additives such as insulating materials, retarders, aggregates, or combinations thereof, which modify the thermodynamic properties of the slurry mixture or the resulting high thermal conductivity composition, or further modify the rheological properties of the slurry mixture.
[0056] If desired or necessary, insulating materials may be present in the slurry mixture of the high thermal conductivity slurry composition to modify the thermal conductivity of the resulting high thermal conductivity composition. This is counterproductive to high thermal conductivity materials, but is also desirable for some geothermal wells near the surface to minimize heat transfer out of the well. Suitable insulating materials may be solid particles with low thermal conductivity. Specific examples of insulating materials suitable for use in the slurry mixture include, but are not limited to, glass (e.g., glass spheres), diatomaceous earth, vermiculite, calcium silicate, polyurethane, polyurethane foam, perlite, glass fiber, rock wool, mineral fiber, cellulose, and any combination thereof.
[0057] In some embodiments, the insulating material may be present in the slurry mixture of the high thermal conductivity slurry composition in an amount effective to impart a desired amount of insulating properties to the slurry mixture. The insulating material may be present in the slurry mixture in an amount of at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight based on the total weight of the slurry mixture. Alternatively, the insulating material may be present in the slurry mixture in an amount of 20% or less, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, or 10% by weight based on the total weight of the slurry mixture. Alternatively, the insulating material may be present in the slurry mixture in an amount of about 1 to about 20%, about 5% to about 15%, or about 7% to about 13% by weight based on the total weight of the slurry mixture.
[0058] In some embodiments, the salts include cations and anions, such as, but not limited to, at least one of lithium, potassium, sodium, hydronium, ammonium, calcium, magnesium, quaternary amines, magnesium, calcium, strontium, barium, titanium, cesium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, aluminum, zirconium, and any combination thereof, and anions, such as, but not limited to, at least one of chloride, bromide, nitrate, iodide, hydroxide, nitrite, hexafluoroantimonate, hexafluoroarsenate, hexafluorophosphate, propionate, lactate, tartrate, phosphate, phosphonium, borate, silicate, sulfate, acetate, aluminate, chromate, dichromate, permanganate, chlorate and perchlorate, formate, or any combination thereof.
[0059] In other embodiments, the retarder may include cationic oligomers or polymers.Such suitable cationic oligomers or polymers include, but are not limited to, at least one monomer comprising imine, alkyleneimine, ethyleneimine, propyleneimine, amine, ethyleneamine, organic amine, quaternary amine, acrylamide, methacrylamide, putrescine, cadaverine, spermidine, spermine, diethylenetriamine, tetramethylenediamine triethylenetetramine, tetraethylenepentamine, diallyldimethylammonium chloride, (2-methacryloyloxyethyl)trimethylammonium chloride, vinylpyrrolidone, derivatives thereof, salts thereof, or combinations thereof.
[0060] The silicates suitable for use as retarders can be of any type suitable for said use, including silicates, oligomeric silicates, polymeric silicates, etc. Examples of suitable silicates include, but are not limited to, alkaline earth metal silicates, alkaline earth metal silicates, and any combination thereof, such as sodium silicate, calcium silicate, potassium silicate, sodium metasilicate, calcium metasilicate, potassium metasilicate, etc.
[0061] In some embodiments, the retarder may be present in the slurry mixture of the high thermal conductivity slurry composition in an amount sufficient to impart a desired amount of swelling reduction to one or more components of the slurry mixture. The retarder may be present in the slurry mixture in an amount of at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight based on the total weight of the slurry mixture. Alternatively, the retarder may be present in the slurry mixture in an amount of 20% or less, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, or 10% by weight based on the total weight of the slurry mixture. Alternatively, the retarder may be present in the slurry mixture in an amount of about 1 to about 20% by weight, about 5% to about 15% by weight, or about 7% to about 13% by weight based on the total weight of the slurry mixture.
[0062] Aggregate may be present in the slurry mixture of the high thermal conductivity slurry composition as a filler. Non-limiting examples of suitable aggregates include sand or quartz sand as described in U.S. Patent Nos. 6,715,543 and 7,258,174, which are incorporated herein by reference in their entirety. In various embodiments, the aggregate may be in the form of a plurality of particles having a broad particle size distribution spanning at least 2 log units, at least 2.5 log units, or at least 3 log units. In some embodiments, the broad particle size distribution of the aggregate, when combined with the high thermal conductivity material, imparts additional integrity to the form or configuration of the high thermal conductivity composition upon compaction or settling of the slurry mixture without the use of a hardening material (e.g., a cement-based material), thereby reducing the permeability of liquids through the high thermal conductivity composition compared to compositions containing particles with a narrow particle size distribution.
[0063] In a particular embodiment, the aggregate is quartz sand. The aggregate may have an average particle size of 0.1 μm to 5.0 mm. The aggregate may be present in the slurry mixture in an amount of at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight based on the total weight of the slurry mixture. Alternatively, the aggregate may be present in the slurry mixture in an amount of 20% or less, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, or 10% by weight based on the total weight of the slurry mixture. Alternatively, the aggregate may be present in the slurry mixture in an amount of about 1 to about 20%, about 5% to about 15%, or about 7% to about 13% by weight based on the total weight of the slurry mixture.
[0064] A method of producing a pumpable slurry is also provided. The method includes combining a high thermal conductivity slurry composition with a large amount of water. The method further includes mixing water with the high thermal conductivity slurry composition, thereby forming a pumpable slurry. The mixing can utilize any method or process, including a static mixer, a rotary mixer, or a recirculating jet mixer. The high thermal conductivity slurry composition slurry mixture has a viscosity that allows the slurry mixture to be pumped to a target location having a target temperature upon addition of water. In certain embodiments, the slurry mixture has a deposition rate of a plurality of particles that allows the slurry mixture to be pumped to a target location upon addition of water without substantial settling of the particles prior to reaching the target location.
[0065] In various embodiments, the amount of water is sufficient to produce a slurry density of about 10 to about 30 pounds per gallon, about 12 to about 25 pounds per gallon, or about 14 to about 16 pounds per gallon. Alternatively, the amount of water is sufficient to produce a slurry density of at least 10 pounds per gallon, at least 12 pounds per gallon, at least 14 pounds per gallon, at least 16 pounds per gallon, at least 18 pounds per gallon, at least 20 pounds per gallon, at least 22 pounds per gallon, at least 24 pounds per gallon, at least 26 pounds per gallon, or 28 pounds per gallon. Alternatively, the amount of water is sufficient to produce a slurry density of 30 pounds per gallon or less, 28 pounds per gallon or less, 26 pounds per gallon or less, 24 pounds per gallon or less, 22 pounds per gallon or less, 20 pounds per gallon or less, 18 pounds per gallon or less, 16 pounds per gallon or less, 14 pounds per gallon, or 12 pounds per gallon.
[0066] The pumpable slurry may have a moisture content of 1-50 gallons / 100 pounds of high thermal conductivity material, 1-40 gallons / 100 pounds of high thermal conductivity material, 1-30 gallons / 100 pounds of high thermal conductivity material, 1-20 gallons / 100 pounds of high thermal conductivity material, or 10-20 gallons / 100 pounds of high thermal conductivity material. Alternatively, the pumpable slurry may have a moisture content of at least 1 gallon / 100 pounds of high thermal conductivity material, at least 5 gallons / 100 pounds of high thermal conductivity material, or at least 10 gallons / 100 pounds of high thermal conductivity material. Alternatively, the pumpable slurry may have a moisture content of no more than 50 gallons / 100 pounds of high thermal conductivity material, no more than 40 gallons / 100 pounds of high thermal conductivity material, or no more than 30 gallons / 100 pounds of high thermal conductivity material.
[0067] 1 and 2 are schematic diagrams illustrating an embodiment of a geothermal well 10 including a well 12 during installation of a pumpable slurry 14A (FIG. 1) and after compression or settling of at least a portion of the pumpable slurry 14A to form a highly thermally conductive composition 14B (FIG. 2). The geothermal well 10 further includes a casing 16 disposed within the well 12 such that an annular space 18 is formed between the well 12 and the casing 16. The pumpable slurry 14A is pumped through (FIG. 1) or located within (FIG. 2) the annular space 18 of the well 12. The geothermal well 10 is formed in an earth formation 20. Upon at least a portion of compression or settling, the pumpable slurry 14A forms a highly thermally conductive composition 14B. In this context, it should be understood that the high thermal conductivity composition 14B of Figure 2 exchanges heat with at least a portion of the casing 16 and at least a portion of the formation 20 surrounding the wellbore 12 via the high thermal conductivity material 24 in the fractures 22. As discussed above, the high thermal conductivity material is in the form of a plurality of particles (which may have a wide particle size distribution) within the wellbore and fractures, which substantially improves thermal contact between the casing 16 and the hot formation at the target location while remaining mobile to minimize damage in the presence of significant forces (e.g., earthquake, thermal expansion and contraction).
[0068] The geothermal well 10 may be connected to a circulation pump (not shown) at ground level above the formation 20. In a preferred embodiment, the formation 20 includes a plurality of fractures 22 that are at least partially filled with a highly thermally conductive material 24. In this context, it should be noted that the highly thermally conductive material 24 in the fractures 22 is in heat exchange with the highly thermally conductive composition 14B in the well 12 and is typically composed of the same material. Among other suitable materials, the highly thermally conductive material 24 in the fractures 22 may be graphite powder, flaked graphite, pyrolytic graphite, desulfurized petroleum coke, graphene, fly ash, copper powder, aluminum nitride, silicon carbide, and any reasonable combination thereof. It will also be appreciated that the highly thermally conductive material 24 is obtained from the pumpable slurry 14A when the pumpable slurry 14A is pumped through the annular space 18 of the well 12 as shown in FIG. 1. Viewed another way, the pumpable slurry 14A in the annular space 18 comprises the same material as the high thermal conductivity material 24 in the fissure 22. In certain embodiments, a secondary conduit 26 defining a return space 28 is disposed within the casing 16. In such a configuration, a second annular space 30 is formed between the casing 16 and the secondary conduit 26. As will be readily appreciated, the casing with the inner secondary conduit forms a closed loop working fluid conduit during operation through which the working fluid is circulated.
[0069] In some embodiments, the placement of the slurry composition is preferably (but not required to be) performed in reverse circulation, as shown in FIG. 1 (and described, for example, in PROCEEDINGS, Thirty-Fifth Workshop on Geothermal Reservoir Engineering, Stanford University, Stanford, California, February 1-3, 2010, which is incorporated herein by reference). For example, as shown in FIG. 1, the slurry 14A is delivered through the annular space 18 to the annular space and fissure 22 at the target location (typically the distal portion of the wellbore), and at least a portion of the slurry exits the target location upwardly through an inner return conduit 26 (typically through a valve or other flow control structure, not shown). Thus, it should be noted that such placement provides a contiguous flow path between the slurry in the fissure and the annular space at the target location, thus providing a continuous path for heat transfer.
[0070] It should further be appreciated that the inner return conduit 26 forms a fluid path 28 for the hot working fluid when the power generation system is operational. The space between the casing 16 and the inner return conduit 26 forms a fluid path 30 that conveys the working fluid to a target location when the power generation system is operational. It should therefore be noted that the fluid path 30 can be used to "flush" any slurry remaining in the inner return conduit 26, as shown in FIG. 2. Direction of the working fluid from the fluid path 30 to 28 can be via valves or other fluid control structures (e.g., using stinger and flapper valves at the ends of tube-in-tube conduits, not shown).
[0071] 3-5 are schematic diagrams illustrating an embodiment of a casing 16 installed in a geothermal well 10, where the well orientation is not vertical (offset relative to normal). The casing 16 may be positioned in any manner known in the geothermal well art. In one embodiment, the casing 16 is centered within the well 12 (FIG. 3). In another embodiment, the casing 16 is partially offset within the well 12 (FIG. 4). In another embodiment, the casing 16 is fully offset within the well 12 (FIG. 5). Advantageously, and as shown in FIGS. 3-5, regardless of the placement of the casing 16, the casing 16 remains at least partially encased by the high thermal conductivity composition 14B. With respect to the remaining figures of FIGS. 3-5, the same numbers refer to the same components as already identified in FIGS. 1-2.
[0072] In certain embodiments, the target location extends in a substantially vertical direction. As used herein, the term "substantially" means that the target location extends toward the center of the Earth, but may be offset from the center by 15 degrees or less, 10 degrees or less, 5 degrees or less, or 1 degree or less. It should be understood that a geothermal well 10 may have multiple target locations, and thus may have both target locations that are substantially vertical and target locations that extend in a direction of at least 30 degrees.
[0073] In view of the above, the inventors contemplate various methods of placing the high thermal conductivity composition 14B within the well 12. In one example, the method may include pumping the pumpable slurry 14A to a target location within the well 12 having a target temperature of at least 200° C., at least 300° C., at least 350° C., at least 400° C., at least 450° C., or at least 500° C. The target location may be at least 500 feet below ground, at least 600 feet, at least 700 feet, at least 800 feet, at least 900 feet, at least 1,000 feet, at least 1,250 feet, at least 1,500 feet, at least 1,750 feet, at least 2,000 feet, at least 2,500 feet, at least 3,000 feet, at least 4,000 feet, or at least 5,000 feet. In these and other embodiments, the pumpable slurry 14A is pumped into the annular space 18 between the wellbore 12 and a casing 16 located within the wellbore 12, thereby displacing fluid within the annular space 18. Most typically, the target location is a dry, hot rock formation, most often with low or little permeability (e.g., intrusive igneous or metamorphic rocks).
[0074] In various embodiments, the pumpable slurry 14A requires agitation (e.g., utilizing a static mixer, a rotary mixer, or a recirculating jet mixer) before being pumped into the well 12. For example, a batch mixer can provide continuous agitation to keep the pumpable slurry 14A fluidized and suspended before being pumped into the well 12. The pumpable slurry 14A may then be fed to a pump that pumps it into the well 12. In various embodiments, the pumpable slurry 14A is delivered to an annular space 18 between the well 12 and a casing 16 disposed in the well 12, thereby displacing fluid within the annular space 18.
[0075] Contemplated methods may also include the further step of removing the displaced fluid through a return space 28 disposed within the casing 16. The fluid may be removed using any method or device known in the art for removing fluid. In various embodiments, the displaced fluid is removed through the return space 28 using a secondary fluid moving from the second annular space 30 to the return space 28. In further embodiments, contemplated methods also include allowing the pumpable slurry 14A to settle or compress in at least a portion of the annular space 18 and the fissure 22, thereby forming a high thermal conductivity composition 14B within the wellbore 12. The pumpable slurry 14A is pumped to a predetermined location, and after pumping, there is at least partial compression of the pumpable slurry 14A at the target location to form the high thermal conductivity compositions 14B and 24 within the wellbore 12 and the fissure 22, respectively.
[0076] With further reference to FIG. 2, during power generating operation of the geothermal well 10, the working fluid travels within the closed loop working fluid conduit (formed in part by the casing 16 and the inner conduit 26) through the second annular space 30 and returns to the surface through the return space 28. However, it should be understood that the flow of the working fluid may be reversed. As the working fluid travels through the second annular space 30, geothermal heat from the target location, conducted by the highly thermally conductive composition 14B and the highly thermally conductive material 24 within the fracture 22, is transferred to the working fluid, thereby increasing the temperature of the working fluid. The working fluid then travels toward the surface through the return space 28. A heat exchanger and turbine generator (both not shown) may be installed in close proximity to the geothermal well 10 to utilize the temperature of the working fluid to generate electrical energy. EXAMPLES
[0077] Tables 1-6 set forth exemplary high thermal conductivity slurry compositions suitable for use herein. However, it should be understood that these compositions are provided merely to illustrate certain embodiments of the inventive subject matter and are not intended to limit the scope of the inventive subject matter.
[0078]
Table 1
[0079]
Table 2
[0080]
Table 3
[0081]
Table 4
[0082]
Table 5
[0083]
Table 6
[0084] In further contemplated embodiments, the inventors believe that at least partial dewatering of the heat transfer slurry system may reduce thermal conductivity, especially when the slurry is placed at a relatively high temperature target location (e.g., at least 250°C, or at least 275°C, or at least 300°C, or at least 325°C, or at least 350°C) and / or when the slurry is surrounded by dry (possibly porous) rock. To mitigate this risk after placement of the non-cementitious slurry, the inventors contemplate continuously or intermittently injecting water under pressure from the surface into the annular space between the casing in the closed loop circuit and the larger casing or wellbore in which the casing is located. Alternatively, water may be supplied to the target location via one or more dedicated conduits extending to or within the compacted or settled non-cementitious high thermal conductivity composition. Depending on the porosity of the settled or compacted slurry, such replenishment of water lost to the formation or evaporation can maintain or improve the thermal conductivity of the settled or compacted slurry without further intervention, helping to maintain peak thermal efficiency of such systems. Alternatively, or in addition, if the porosity (or water permeability) of the settled or compacted slurry is very low, it is envisioned that the slurry composition can be adjusted to increase or decrease permeability as needed to achieve the required flow rate of water from the surface to depth. As will be readily appreciated, such adjustments will depend on the expected rate of water loss, the porosity of the surrounding formations, temperature, etc., and one skilled in the art can readily adjust the permeability following quantitative protocols, such as may be found in ASTM D4630-19.
[0085] Thus, in at least some embodiments, the non-cementitious, high thermal conductivity composition has a permeability to water that allows water to penetrate through at least 50%, or at least 60%, or at least 70%, or at least 75%, or at least 80%, or at least 85%, or at least 90% of the compacted or settled non-cementitious, high thermal conductivity composition, resulting in a potential loss in thermal conductivity (compared to the thermal conductivity immediately after installation) of less than 30%, or less than 25%, or less than 20%, or less than 15%, or less than 10%, or even lower after at least 1 year, or at least 3 years, or at least 5 years, or at least 7 years, or at least 10 years.
[0086] In some embodiments, numerical values expressing properties such as amounts and concentrations of ingredients, reaction conditions, etc., used to describe and claim certain embodiments of the present invention are understood to be modified in some cases by the term "about". As used herein, the terms "about" and "approximately", when referring to a specified measurable value (parameter, amount, time duration, etc.), are meant to encompass the specified value and variations from the specified value, for example, variations of ±10% or less, or ±5% or less, or ±1% or less, or ±0.1% or less of the specified value, as appropriate for implementation in the disclosed embodiments. Thus, the values themselves to which the modifier "about" or "approximately" refers are specifically disclosed. The description of ranges of values herein is intended merely to serve as a shorthand method of referring individually to each individual value falling within the range. Unless otherwise stated herein, each individual value is incorporated herein as if it were individually set forth herein.
[0087] All methods described herein may be performed in any suitable order unless otherwise indicated herein or clearly contradicted by context. Any examples provided herein with respect to specific embodiments, or the use of exemplary language (e.g., "such as"), are intended merely to better illustrate the invention and are not intended to impose limitations on the scope of the otherwise claimed invention. No language in this specification should be construed as indicating any non-claimed element essential to the practice of the invention.
[0088] As used throughout this specification and the claims that follow, the meanings of "a," "an," and "the" include plural references unless the context clearly indicates otherwise. Also, as used herein, the meaning of "in" includes "in" and "on," unless the context clearly indicates otherwise. As used herein, and unless the context clearly indicates otherwise, the term "coupled to" is intended to include both direct coupling (wherein the two elements that are coupled to each other contact each other) and indirect coupling (wherein at least one additional element is disposed between the two elements). Thus, the terms "coupled to" and "coupled with" are used interchangeably.
[0089] It will be apparent to those skilled in the art that many more modifications than already described are possible without departing from the inventive concepts herein. Accordingly, the subject matter of the present invention is not limited except as by the appended claims. Moreover, in interpreting both the specification and the claims, all terms should be interpreted in the broadest possible manner consistent with the context. In particular, the terms "comprises" and "comprising" should be interpreted as referring to elements, components, or steps in a non-exclusive manner, indicating that a referenced element, component, or step may be present, utilized, or combined with other elements, components, or steps not expressly referenced. When the specification or claims refer to at least one selected from the group consisting of A, B, C...... and N, the sentence should be interpreted as requiring only one element from the group, and not A+N, B+N, etc.
Claims
1. A highly thermally conductive slurry composition comprising: A slurry mixture including a high thermal conductivity material and an optional dispersant, the high thermal conductivity material is in the form of a plurality of particles having a broad particle size distribution; The broad particle size distribution spans at least two logarithmic units; the high thermal conductivity material is present in an amount effective such that upon compression or settling of the slurry mixture at a target location, the slurry composition has a thermal conductivity of at least 3 W / m°K; Slurry Composition.
2. The composition of claim 1 , wherein the slurry mixture further comprises at least one functional agent.
3. 3. The composition of claim 2, wherein the functional agent is selected from the group consisting of plasticizers, surfactants, organic polymers, silica fillers, NaCl or KCl or other inorganic salts, and clays.
4. 2. The composition of claim 1, wherein the broad particle size distribution spans at least 3 log units.
5. 2. The composition of claim 1, wherein the broad particle size distribution is from 0.1 μm to 5.0 mm.
6. 6. The composition of any one of claims 1 to 5, wherein the high thermal conductivity material is selected from the group consisting of graphite powder, flake graphite, pyrolytic graphite, desulfurized petroleum coke, graphene, fly ash, copper powder, aluminum nitride, and silicon carbide.
7. 10. The composition of claim 1, wherein the high thermal conductivity material is present in the slurry mixture in an amount of at least 10% by weight by volume.
8. 10. The composition of claim 1, wherein the high thermal conductivity material is present in the slurry mixture in an amount of at least 30% by weight.
9. 10. The composition of claim 1, wherein the high thermal conductivity material is present in an amount effective such that the slurry mixture upon compaction or settling at the installation site has a thermal conductivity of at least 4 W / m°K.
10. 10. The composition of claim 1, wherein the high thermal conductivity material is present in an amount effective such that the slurry mixture upon compaction or settling at the installation site has a thermal conductivity of at least 15 W / m°K.
11. 10. The composition of claim 1, wherein the slurry mixture has a deposition rate of the plurality of particles that, upon addition of water, enables the particles to be pumped to the target location without substantial settling of the particles prior to reaching the target location.
12. A pumpable slurry, comprising the highly thermally conductive slurry composition according to any one of claims 1 to 11 mixed with water.
13. 13. The pumpable slurry of claim 12 having a density of 10 to 30 pounds per gallon.
14. 14. The pumpable slurry of claim 12 or 13, having a moisture content of 1-20 gallons / 100 pounds of high thermal conductivity material.
15. 1. A method for producing a pumpable slurry, comprising: Combining the high thermal conductivity slurry composition of claims 1 to 11 with a large amount of water; and mixing the water with the high thermal conductivity slurry composition to form the slurry, the amount of water being sufficient to produce a slurry density of 10-30 pounds per gallon; A manufacturing method comprising:
16. 16. The method of any one of claims 15 to 16, further comprising the step of supplying the pumpable slurry to a pump that pumps the slurry to a well.
17. 17. The method of claim 16, wherein the step of pumping the slurry into the well is performed at a velocity that allows for at least partial compaction or settling of the slurry mixture at the target location.
18. 1. A method for installing a highly thermally conductive composition in a well, comprising: pumping the pumpable slurry of any one of claims 12 to 14 to a target location having a target temperature of at least 200°C, said pumpable slurry being delivered to an annular space between said wellbore and a casing located within said wellbore, thereby displacing fluid within said annular space; removing the displaced fluid through a return space located within the casing; and compressing the pumpable slurry in at least a portion of the annular space to form the high thermal conductivity composition in the wellbore, the high thermal conductivity composition exchanging heat with at least a portion of the casing and at least a portion of the formation surrounding the wellbore, pumping the pumpable slurry to a predetermined location, and at least partially compressing or settling the slurry at the target location after pumping; A method comprising:
19. 20. The method of claim 18, wherein the target location is at least 3,000 feet below ground.
20. The method of claim 18 , wherein the target locations extend in a substantially vertical direction.
21. 20. The method of claim 18, wherein the return space located within the casing is enclosed within a secondary conduit located within the casing, and a second annular space is formed between the casing and the secondary conduit.
22. 22. The method of claim 21, wherein the step of removing the displaced fluid through the return space uses a second fluid moving from the second annular space to the return space.
23. 23. The method of any one of claims 18-22, wherein the formation includes a plurality of fractures at least partially filled with a high thermal conductivity material, and the high thermal conductivity material in the fractures exchanges heat with the compressed high thermal conductivity composition in the wellbore.
24. 24. The method of claim 23, wherein the high thermal conductivity material in the cracks is selected from the group consisting of graphite powder, flake graphite, pyrolytic graphite, desulfurized petroleum coke, graphene, fly ash, copper powder, aluminum nitride, and silicon carbide.
25. 20. The method of claim 18, further comprising pumping water into the at least partially compressed or settled slurry at the target location after the slurry has been compressed or settled to maintain or increase a thermal conductivity of the compressed or settled slurry at the target location.
26. 1. A method for reducing thermal conduction losses in a non-cementitious, highly thermally conductive composition in a well, comprising: providing water in situ to the non-cementitious, high thermal conductivity composition, where the non-cementitious, high thermal conductivity composition compacts or settles at the target location, the water being provided in an amount sufficient to reduce loss of thermal conductivity of the non-cementitious, high thermal conductivity composition compared to when the non-cementitious, high thermal conductivity composition was installed; A method comprising:
27. 27. The method of claim 26, wherein the water is supplied through an annular space between a casing and a wellbore wall or wellbore casing in a closed loop circuit.
28. 27. The method of claim 26, wherein the non-cementitious, high thermal conductivity composition has a permeability to water that allows water to penetrate through at least 75% of the compacted or settled non-cementitious, high thermal conductivity composition.
Citation Information
Patent Citations
Glass ceramic composition, substrate for light emitting element, and light emitting device
JP2015120621A
Effect of particle size on the hydraulic conductivity of geothermal grout systems
US20210071063A1
Heat-conductive resin composition and heat dissipation sheet
WO2021251494A1
Construction and operation of conductive and convective geothermal wells
WO2022018674A1
Geothermal well using graphite as solid conductor
US20110232858A1
Cited By
Method of pulverizing molybdenum disulfide using dispersant and method of preparing high grade molybdenum disulfide from low grade molybdenite concentrate using the same
KR102997437B1
Ground Convection Heat Exchanger-Type Heat Pump System
KR103017931B1